Hubungan Kesepian dengan Nomophobia pada Mahasiswa Merantau dalam Menyelesaikan Tugas Akhir di UIN Sjech M. Djamil Djambek Bukittinggi - Keysha Nabila Aulia Purba; Fadhilla Yusri; Afrinaldi Afrinaldi; Alfi Rahmi (YASIN, 2026)
Technological developments, particularly the use of smartphones, provide convenience in daily life but also have the potential to cause psychological problems, one of which is nomophobia. One factor assumed to be related to nomophobia is loneliness, especially among migrant students who are completing their final projects. This study aims to determine the relationship between loneliness and nomophobia among migrant students of the 2021 cohort of the Faculty of Tarbiyah and Teacher Training at UIN Sjech M. Djamil Djambek Bukittinggi. This study used a quantitative approach with a correlational method. The research sample consisted of 58 respondents selected using purposive sampling based on the research criteria. Data were collected using a 42-item loneliness questionnaire and a 33-item nomophobia questionnaire with a 1–4 Likert scale. The data were analyzed using the Pearson Product Moment correlation test. The results showed a significant positive relationship between loneliness and nomophobia among migrant students who were completing their final projects, with a correlation coefficient of 0.402 and a significance value of 0.002 < 0.05. These findings indicate that the higher the level of loneliness, the higher the tendency toward nomophobia, with a moderate level of relationship. The conclusion of this study affirms that loneliness is a psychological factor related to nomophobia among migrant students in the process of completing their final projects. The implications of this study emphasize the importance of higher education institutions paying attention to psychosocial support for migrant students and strengthening literacy on healthy and adaptive smartphone use.